Learning not to underestimate: Understanding the dynamics of women's underestimation in groups. Issue 7 (8th October 2018) - Meslec, Nicoleta; Aggarwal, Ishani
Abstract : Purpose: The purpose of this paper is twofold. First, it aims to isolate a new mechanism (i.e. underestimation judgments) through which gender (percentage of women in a group in particular) influences group synergy, or the extent to which groups are able to perform better than their composing members. Second, it aims to explore further the extent to which underestimation judgments are prone to change and adjustment as a result of participating in social contexts, such as groups. Design/methodology/approach: The sample consisted of 278 student participants (161 women), nested within 66 groups. Participants performed a series of cognitive tasks with correct answers and had to rate how confident they were in the answers given. Findings: Gender composition in terms of percentage of women is positively related to underestimation within groups and this negatively affects group synergy. The data also show that women underestimate less or improve the accuracy of their performance self-evaluation judgments after group interaction, thereby highlighting a factor (group experience) that helps women gain greater accuracy about their performance. Research limitations/implications: Further research could explore the extent to which underestimation judgments are present in various organizational contexts and the extent to which they are prone to change. Practical implications: Organizations and universities are invited to reflect on the relevance of self-beliefs (and underestimation in particular) on the accomplishment of cognitive tasks. Practices and policies should be geared toward the enhancement of self-knowledge accuracy, with a particular focus on the female population. Originality/value: This paper identifies a new mechanism through which gender influences group synergy: underestimation judgments.